THE FACTORS AFFECTING VISITOR SATISFACTION AT BONE GYM BENGKULU CITY - Chintia Rahmadani; Ida Anggriani; Meiffa Herfianti (Jurnal Ekonomi, Manajemen, Akuntansi dan Keuangan, 2020)
In this competition era, hope and wish for satisfaction for services is becoming a weapon for GYM business and it must be maintained and improved. The purpose of this research is to find put the factors which affect the visitor satisfaction at Bone GYM in Bengkulu city. Analysis method in this research is rating scale method. Sample in this research are 68 respondents. The result of this research shows that the product quality factor is 307 in interval 285,6-340 with criteria strongly agreed. Services quality factor is 295,6 on interval 285,6-340 with criteria strongly agreed. Emotional factor is 295,6 which is on interval 285,6-340 with criteria strongly agreed. Price factor is 296,2 which is on interval 285,6-285,6 with agreed category. Dominant factor which affect visitor satisfaction is product quality with score 307.